(3QSGdI aj abg GdRjOjIs - (3RjO Hf Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH , CHh GdMSjf GdYdhqj GdgGTej GdbQTj , hjbGd dg (B((3RjO GdTgjO(B) (3, (B122 (3g` s ((3eMeO CMSf Hf CMSf GdYdai s)
(3ChdgG (B:s
(3jHOC HcJGH GdWgGQI HGH GdhVhA s
(3BNQgG (B:s
(3jfJgi HHGH cQGgjI CNP GdTYQ EPG ONd ThGd eef CQGO GdML s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdaGJjcGf s
Keywords: (3Gdabg GdESdGejs